2011
DOI: 10.1111/j.1439-0426.2011.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of Capoeta damascina (Valenciennes, 1842), a cyprinid fish, in Zayandeh-Roud River, Iran

Abstract: Summary Reproductive characteristics of siahmahi, Capoeta damascina (Valenciennes, 1842), a native cyprinid in the Zayandeh‐Roud River, were investigated by monthly sampling from March 2007 to April 2008. Among 689 specimens captured, the overall sex ratio was 1 : 1.57 (males : females). Males matured at age 2+. Females matured between ages 4 and 6, with 100% maturity at age 7+. Based on the gonadosomatic index (GSI), the reproductive period peaked between May and June. Histological and macroscopic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Age of first sexual maturity in this study was ˂ 2 + for males and 3 + years for females. Age at sexual maturity of C. damascina living in Iranian waters was reported as 2 + and 4 + for males and females (Soofiani and Asadollah 2010;Asadollah et al 2011). In the present study, the smallest mature male and female fish were 11.5 and 18.5 cm, respectively.…”
Section: Fecundity and Oocyte Diametersmentioning
confidence: 64%
See 4 more Smart Citations
“…Age of first sexual maturity in this study was ˂ 2 + for males and 3 + years for females. Age at sexual maturity of C. damascina living in Iranian waters was reported as 2 + and 4 + for males and females (Soofiani and Asadollah 2010;Asadollah et al 2011). In the present study, the smallest mature male and female fish were 11.5 and 18.5 cm, respectively.…”
Section: Fecundity and Oocyte Diametersmentioning
confidence: 64%
“…Stoumboudi et al (1993) in Jordan River reported similar results. This ratio for C. damascina in other areas were in favour of females (Mazaheri 2007;Soofiani and Asadollah 2010;Asadollah et al 2011). Differences in sex ratio might be related to the interspecific differences in adapted population of a species to different ecological conditions, different in the date and time of capture, fishing gear, location, different growth rates and different mortalities in males and females, migration of mature fishes from the region and different behavior pattern in male and female fish (Qasim 1966;Fishelson et al 1996;Keivany and Soofiani 2004;Soofiani et al 2006;Asadollah et al 2011;Keivany et al 2012;Abaszadeh et al 2013;Tabatabaei et al 2014;Keivany and Daneshvar 2015).…”
Section: Fecundity and Oocyte Diametersmentioning
confidence: 99%
See 3 more Smart Citations